Functional Interface for Glycoprotein Sensing Focusing on Biosensors - Qu, Ke (Langmuir : the ACS journal of surfaces and colloids, 2024)
Glycosylated proteins or glycoproteins make up a large family of glycoconjugates, and they participate in a variety of fundamental biological events. Glycoproteins have become important biomarkers in the diagnosis and treatment of a number of tumors. Biosensors are quite suitable for glycoprotein detection. The design and fabrication of a functional sensing interface play a crucial role in the biosensor construction to target glycoproteins. The functional interface, particularly receptors, typically determines the key characteristics of a biosensor, such as selectivity and sensitivity. Antibody, peptide, aptamer, boronic acid derivative, lectin, and molecularly imprinted polymer are all capable receptors for glycoprotein recognition, and each of these will be discussed. Most glycoproteins exist in low abundance, thus rendering signal amplification techniques indispensable. Nucleic acid-mediated and nanomaterial-mediated signal amplification for the detection of glycoproteins will be focused on herein. This review aims to highlight these different functional interfaces for glycoprotein sensing